Relationship between Environmental Factors and Rheumatic Heart Disease - Tobing, Tina Christina Lumban; Ontoseno, Teddy; Rahayuningsih, Sri; Ganie, Ratna Akbari; Siregar, Yahwardiah (Open Access Macedonian Journal of Medical Sciences, 2021)
Background. Rheumatic fever (RF) and rheumatic heart disease (RHD) are the most common acquired heart diseases in children. Environmental factors have been reported to play an important role in RHD’s prevalence Aim. The main purpose of this study is to assess the associations between environmental factors and RHD in children. Methods. A case control study was conducted in the Department of Child Health, Haji Adam Malik Hospital from April to June 2017. The case group consisted of children aged 5-18 years with RHD while control group consisted of healthy children. Demographic, anthropometric, and laboratory data were collected along with environmental factors. Statistical analysis was done using Statistical Product and Service Solution (SPSS). A P value of <0,05 with 95% confidence interval was considered significant. Results. A total of 39 children were enrolled in each group. Subjects’ father who only went to elementary and junior high school had a higher risk of having children with RHD (OR 28; p = 0.032 and OR 15.75; p = 0.011, respectively). Subjects’ mother who only went to junior high school had 7 times higher risk of having children with RHD (p = 0.026). Low monthly income increased the risk of RHD (OR 3,68; p = 0,009). Tap water usage, meat consumption more than once per week, and feasibility to buy clothes >1 pair per year decreased the risk of RHD at 0,31 (p = 0,013), 0,3 (p = 0,016), and 0,04 times (p <0,001) respectively. Conclusion. Parent’s education, monthly family income, water source, frequency of meat consumption, and feasibility to buy clothes are related to RHD in children.